The Roles of Purchase Intentions and Social Media in Dark Tourism (2023)
Dark tourism is roughly understood as travelling to places historically associated with death and tragedy. However, the determinants of such a specific type of tourism are not well explored. Therefore, this research aims to determine the possible relation between the intention variables, particularly perceived risk and the values of sensation-seeking and hedonism. For this purpose, an online questionnaire of eight subscales was applied to 821 participants, with ages corresponding to generations Y and Z. The results of a structural equation modelling revealed the existence of seven latent variables whose goodness-of-fit suggests that dark tourism is mainly related to the intention to visit and search for information on the Internet. This study is novel compared to previous research in that it suggests that the destination does not have a direct relation to the intention to share information on social media.